(untitled) (Researcher: A Research Journal of Culture and Society, 2021)
Corruption needs to be prevented and tackled not only because of its foul but also economically causes financial losses to the state and is a violation of the rights of the social and economic community. This paper is based on the growing need to eradicate corruption in society. The forms and causes of corruption, how to combat it, and what are the challenges to eradicating corruption are issues that are on the increase on national, regional, and international agendas. Transparency International Nepal, The United Nations Convention against Corruption, Commission for the Investigation of Abuse of Authority (CIAA), Nepal, the United Nations Convention against Transnational Organized Crime, U4 – Chr. Michelsen Institute (CMI), the United Nations Declaration against Corruption and Bribery in International Commercial Transactions, and the International Code of Conduct for Public Officials are living testimonies. These calls to eradicate corruption present puzzles that scholarly investigations need to take the lead role and center stage in unraveling. This scenario reveals and demands both theoretical and practical discourse, understanding the concept of e-Government, its necessities, and challenges to implementing it.